USING MIND MAPPING IN TEACHING THE PLOT OF A NOVEL - Dwi Ratnasari (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2014)
Abstract: This paper discusses about using Mind Mapping in teaching the plot of a novel. This study used a one-group quasi experimental with equivalent time-samples design and was conducted on a group of Form 5 students in one of the schools in Johor Bahru district. The instruments utilized in the inquiry were tests. The results showed that Mind Mapping method did improve the students’ understanding by having them focus not only on the main ideas but also on the elaborations and examples that are stated in the novel. With examples and elaborations, students would find it easier to understand the events in the novel. Key words: mind mapping, plot, novel